2020
DOI: 10.1128/aac.00559-20
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Cefiderocol Alone and in Combination with Levofloxacin, Minocycline, Polymyxin B, or Trimethoprim-Sulfamethoxazole against Multidrug-Resistant Stenotrophomonas maltophilia

Abstract: Objectives: The production of a metallo-(L1) and serine-(L2) β-lactamase precludes the use of β-lactams for the treatment of Stenotrophomonas maltophilia infections. Pre-clinical data suggest cefiderocol is the first approved β-lactam with reliable activity against S. maltophilia, but data against strains resistant to current first -line agents are limited and no studies have assessed cefiderocol-based combinations. The objective of this study was to evaluate and compare the in vitro activity of cefiderocol al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…In SIDERO-CR, 1873 carbapenem–nonsusceptible isolates, including Enterobacterales, MDR A. baumannii , MDR P. aeruginosa , and S. maltophilia were collected globally between 2014 and 2016. In vitro data are also available from other studies assessing cefiderocol against a wide range of clinically important isolates collected globally [ 14 , 28 30 ] and from Canada [ 31 ], Germany [ 32 ], Greece [ 33 ], Japan [ 34 , 35 ], Spain [ 36 ], Taiwan [ 37 ], the UK [ 38 ] and the USA [ 17 , 39 42 ].…”
Section: Pharmacodynamic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In SIDERO-CR, 1873 carbapenem–nonsusceptible isolates, including Enterobacterales, MDR A. baumannii , MDR P. aeruginosa , and S. maltophilia were collected globally between 2014 and 2016. In vitro data are also available from other studies assessing cefiderocol against a wide range of clinically important isolates collected globally [ 14 , 28 30 ] and from Canada [ 31 ], Germany [ 32 ], Greece [ 33 ], Japan [ 34 , 35 ], Spain [ 36 ], Taiwan [ 37 ], the UK [ 38 ] and the USA [ 17 , 39 42 ].…”
Section: Pharmacodynamic Propertiesmentioning
confidence: 99%
“…maltophilia [ 17 , 28 , 31 , 33 , 37 , 38 , 40 , 41 ]. In MDR strains of Enterobacterales, P. aeruginosa and S. maltophilia , cefiderocol susceptibility was > 95% [ 33 , 36 , 39 , 40 ].…”
Section: Pharmacodynamic Propertiesmentioning
confidence: 99%
“…Apart from cefiderocol, minocycline was the most active agent, with 100% of isolates being susceptible. [49][50][51] Similarly, 100 blood isolates of S. maltophilia revealed MICs of £1 mg/L for cefiderocol and superior susceptibility compared to ceftazidime, ceftazidime/avibactam, and ceftolozane/tazobactam. 27 Cefiderocol also showed superiority compared to aminoglycoside and carbapenem-resistant species with MICs ranging from £0.03 to 0.25 mg/L, with the MIC 90 being 0.25 mg/L.…”
Section: S Maltophiliamentioning
confidence: 99%
“…Cefiderocol is a novel, parenteral siderophore cephalosporin which is active against Gram-negative, nonfermenting pathogens, including S. maltophilia , even in the presence of carbapenemases due to its stability against these hydrolyzing enzymes ( 12 ). Cefiderocol has shown potent in vitro activity against a range of carbapenem-susceptible and carbapenem-resistant (CR) Gram-negative bacteria collected from around the world, including S. maltophilia strains resistant to other commonly used antibiotics ( 13 16 ). Preclinical studies have already demonstrated that cefiderocol is effective in murine thigh ( 17 ) and rat lung ( 18 ) infection models, and this in vivo efficacy appears to correspond well with its in vitro activity.…”
Section: Introductionmentioning
confidence: 99%